2019
DOI: 10.22630/pniks.2019.28.2.16
|View full text |Cite
|
Sign up to set email alerts
|

Identification of factors shaping tender prices for lightweight

Abstract: A reliable estimation of the tender prices for lightweight curtain walls is a complex and time-consuming process for the contractor, as it depends on many factors related to both the technical parameters of the designed façade and the investor’s requirements for the solutions selected. The aim of the paper is to identify the factors affecting the costs of manufacturing lightweight curtain walls. Data regarding the complexity of curtain wall construction costs was obtained on the basis of the analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The authors identified cost factors with the analysis of project and cost documentation and as-built settlements for cases, as well as direct interviews with contractors and investors. The factor identification studies presented in this paper constitute an extension of the preliminary studies, the results of which have been previously presented [18]. Finally, the completed study included 80 cases of public buildings constructed in the years 2013-2019 in Poland.…”
Section: Identified Cost Factorsmentioning
confidence: 96%
See 2 more Smart Citations
“…The authors identified cost factors with the analysis of project and cost documentation and as-built settlements for cases, as well as direct interviews with contractors and investors. The factor identification studies presented in this paper constitute an extension of the preliminary studies, the results of which have been previously presented [18]. Finally, the completed study included 80 cases of public buildings constructed in the years 2013-2019 in Poland.…”
Section: Identified Cost Factorsmentioning
confidence: 96%
“…The core of the facade is made of aluminium sections, while the filling is glass. The most frequently used systems are mullion-transom, semistructural, and structural systems [18]. Types of aluminium-glass facades are illustrated in Figure 1.…”
Section: Short Characteristic Of Selected Facade Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of new technologies is visible in contemporary works, including the implementation of BIM standards in the construction investment process [27], or the use of information from the "Big Data" [6]. The authors of many papers describe the implementation of the results of their research to the construction industry [9,18,19,24], cost of construction works [13,17,21,25], risk in construction [15,16,23]. One example combining the practical aspect and high research potential are the Bayesian Networks.…”
Section: Introductionmentioning
confidence: 99%